Improving Constructing Child Friendly School Culture Through Symbolic Interaction - Fritz Hotman Syahmahita Damanik; Oman Sukmana; Tri Sulistyaningsih (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
School culture is not a static institutional given but a dynamic social achievement produced and reproduced through the everyday interpretive interactions of all stakeholders: teachers, students, parents, and administrators. This article investigates how the concept of